Optimasi Parameter Pengukuran Dimensi dan Defect Ubin Keramik dengan Metode Taguchi - Denny Sukma Eka Atmaja; Muhammad Kusumawan Herliansyah (Jurnal Sistem Cerdas, 2021)
The ceramics industry in Indonesia has a large contribution to the growth of various aspects in Indonesia. But in reality, there is still an imbalance between exports and imports for ceramic products. One way is to improve the quality of the ceramic industry in Indonesia. In fact, the ceramic quality inspection process in the ceramic industry is still done manually which can make mistakes in identifying defects. In this study, the design of variable identification system of ceramics was carried out specifically in the area of ceramics and dry spot defects on ceramic surfaces using image processing. Whereas to get a low error rate against the applicable variables, a design of experiment with the Taguchi approach is carried out. The results show that 50 cm distance, 300 lux light, 1x resize and 0.06 threshold can produce an image that has the smallest error value when identifying ceramic area and dry spot defects on the ceramic surface.